THE PAST AND PRESENT OF PARAOXONASE ENZYME: ITS ROLE IN THE CARDIOVASCULAR SYSTEM AND SOME DISEASES - Aydin, Suleyman; Sahin, Ibrahim; Aydin, Suna; Aksoy, Aziz; Citil, Cihan (De Gruyter Poland Sp Zoo, 2012)
Although paraoxonase is synthesized in many tissues including the heart, colon, kidneys, lungs, small intestines and brain, its major locus of synthesis is the liver. PON1 is in close association with apolipoproteins and protects LDL against oxidation. It was reported that PON1 quantities dropped to 40 times lower than normal in cardiovascular diseases and diseases like diabetes, ulcerative colitis, Crohn's disease, chronic renal failure, SLE, Behcet's disease, cancer, hepatitis B, obesity, metabolic syndrome, Alzheimer's and dementia. It is speculated that the concerning decline in se rum PON1 amount results from single nucleotide polymorphism in the coding (Q192R, L55M) and promoter (T-108C) sites of the PON1 gene. Additionally, circulating amounts of PON1 are affected by vitamins, antioxidants, fatty acids, dietary factors, drugs, age and lifestyle. This collection attempts to review and examine the past and present studies of paraoxonase and its relation with the cardiovascular system and some relevant diseases.
Keywords: paraoxonase; polymorphism; cardiovascular system diseases